Common Fixed Point Theorems in Multiplicative Metric Spaces satisfying E.A. property and (CLR) property for Rational Contractive Map - Manoj Kumar; Kamal Kumar; Nisha Sharma; Rajeev Jha; Arti Mishra (International Journal of Mathematics And its Applications, 2016)
In this paper we prove common fixed point theorems for weakly compatible mappings along with E.A property and common limit range properties using Rational contraction satisfying implicit functions in multiplicative metric space.